The Law and Policies with Regard to Foreign Purchase of Land in the Country with Special Reference to Johor - Awang, Adibah (1993)
Prior to March 25, 1985, there was no restriction as far as origin, race and citizenship went with regard to ownership of land in Malaysia. Pursuant to Act A587 oj 1984, Part Thirty-Three (A) was inserted in the National Land Code, the effect of which was to impose restrictions on foreign ownership of landed properties. In the case of land subject to the category "agriculture", there was an absolute prohibition on its disposal and a restriction on its dealings in favour of foreigners. But in the Case of land subject to the category "building ", a disposal could be effected in favour of a non-citizen upon the prior written consent of the State Authority. Any acquisition of land in contravention Of these provisions shall be null and void. However, land subject to the category "industry" can be acquired freely by the foreigners. Part Thirty Three (A) unfortunately, had a short life span and was repealed in less than two years via Act A658/ 1986, with effect from ]anumy 1, 1987 giving effect to no limitation as far as foreign ownership was concerned. Now, we are witnessing another set of Part Thitty-Three (A), reintroduced, with certain modifications to the repealed 1984 version, via, Act A832, and gazetted on 16. 7.92. The writer seeks to give an overview of the law and policies prior to the 1992 Amendment and the present position with regard to foreign purchase of land in this country.